Building the Pamir‐Tibetan Plateau—Crustal stacking, extensional collapse, and lateral extrusion in the Central Pamir: 2. Timing and rates. Issue 3 (8th March 2017) - Rutte, Daniel; Ratschbacher, Lothar; Khan, Jahanzeb; Stübner, Konstanze; Hacker, Bradley R.; Stearns, Michael A.; Enkelmann, Eva; Jonckheere, Raymond; Pfänder, Jörg A.; Sperner, Blanka; Tichomirowa, Marion
Abstract: Geothermochronologic data outline the temperature‐deformation‐time evolution of the Muskol and Shatput gneiss domes and their hanging walls in the Central Pamir. Prograde metamorphism started before 35 Ma and peaked at 23–20 Ma, reflecting top‐to‐ N thrust‐sheet and fold‐nappe emplacement that tripled the thickness of the upper 7–10 km of the Asian crust. Multimethod thermochronology traces cooling through 700–100°C between 22 and 12 Ma due to exhumation along dome‐bounding normal‐sense shear zones. Synkinematic minerals date normal sense shear‐zone deformation at 22–17 Ma. Age‐versus‐elevation relationships and paleoisotherm spacing imply exhumation at ≥3 km/Myr. South of the domes, Mesozoic granitoids record slow cooling and/or constant temperature throughout the Paleogene and enhanced cooling (7–31°C/Myr) starting between 23 and 12 Ma and continuing today. Integrating the Central Pamir data with those of the East (Chinese) Pamir Kongur Shan and Muztaghata domes, and with the South Pamir Shakhdara dome, implies (i) regionally distributed, Paleogene crustal thickening; (ii) Pamir‐wide gravitational collapse of thickened crust starting at 23–21 Ma during ongoing India‐Asia convergence; and (iii) termination of doming and resumption of shortening following northward propagating underthrusting of the Indian cratonic lithosphere at ≥12 Ma. Westward lateral extrusion of Pamir Plateau crust into the Hindu Kush and the Tajik depression accompanied all stages. Deep‐seated processes, e.g., slab breakoff, crustal foundering, and underthrusting of buoyant lithosphere, governed transitional phases in the Pamir, and likely the Tibet crust. Key Points: South and Central Pamir crust thickened from >37 to 22 Ma and since 12 Ma by thrust‐sheet and fold‐nappe emplacement Northward crustal collapse formed the Central Pamir gneiss domes at 22‐ ≥12 Ma by N‐S extension during ongoing India‐Asia convergence Pamir crustal evolution was governed by Indian slab breakoff and subsequent shallow underthrusting of cratonic Indian lithosphere